Paris for one and other stories - Moyes, Jojo, 1969- (Pamela Dorman Books/Viking, 2016)
"From the #1 New York Times bestselling author of Me Before You and After You, a sensational collection featuring the title novella and eight other stories. Quintessential Jojo Moyes, Paris for One and Other Stories is an irresistibly romantic collection filled with humor and heart. Nell is twenty-six and has never been to Paris. She's never even been on a romantic weekend away--to anywhere--before. Everyone knows travelling abroad isn't really her thing. But when Nell's boyfriend fails to show up for their romantic mini-vacation, she has the opportunity to prove everyone--including herself--wrong. Alone and in Paris, Nell uncovers a version of herself she never knew existed: independent and intrepid. Could this turn out to be the most adventurous weekend of her life? Funny,charming, and irresistible,Paris for One is vintage Moyes--as are the other stories that round out the collection"--